2022
DOI: 10.6008/cbpc2179-6858.2022.002.0006
|View full text |Cite
|
Sign up to set email alerts
|

What does the evidence for COVID-19 in dogs and cats point to? An investigation in the literature

Abstract: In view of current COVID-19 pandemic scenario, uncertainties still remains around the role of domestic animals on COVID-19 epidemiology, this systematic review aims to present the scientific evidence available, so far, on dogs and cats epidemiological role in the COVID-19 pandemic. The systematic review was conducted in accordance with the recommendations of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses – PRISMA. Selected studies reports negative results of dogs and cats both in serolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
2
0
0
Order By: Relevance
“…Corroborating the data of this study, other authors have identified a low prevalence of COVID-19 among pets in Brazil and in other countries [ 54 ]. Stevanovic et al .…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Corroborating the data of this study, other authors have identified a low prevalence of COVID-19 among pets in Brazil and in other countries [ 54 ]. Stevanovic et al .…”
Section: Resultssupporting
confidence: 83%
“…Corroborating the data of this study, other authors have identified a low prevalence of COVID-19 among pets in Brazil and in other countries [54]. Stevanovic et al [55] reported that seropositivity among companion animals in Croatia is low, especially when compared to the results from China.…”
Section: Number (%) Of Dogs Positive For Canine Coronavirussupporting
confidence: 76%